Glycogen storage disease type Ib: modern understanding of the pathogenesis of neutropenia and prospects for its treatment with empagliflozin - Andrej N. Surkov; Aleksandr A. Baranov; Lejla S. Namazova-Baranova; Anna L. Arakelyan; Evgenij E. Bessonov; Natal’ya V. Zhurkova (Педиатрическая фармакология)
Glycogen storage disease type Ib (GSD Ib) — is a disease from the group of hereditary metabolic diseases caused by insufficiency of the glucose-6-phosphate transporter (G6PT, SLC37A4), which leads to a violation of both glycogenolysis and gluconeogenesis and, as a consequence, to excessive accumulation of glycogen and fat in the liver, kidneys and intestinal mucosa. The main clinical manifestations and laboratory data include growth retardation, hepatomegaly, hypoglycemia, lactic acidosis, hyperuricemia and hyperlipidemia. Complications of this disease are hepatocellular adenoma with a possible risk of malignancy, nephropathy and osteoporosis. A specific sign of GSD Ib is neutropenia with impaired neutrophil function, which creates prerequisites for recurrent infections and the development of inflammatory bowel disease. Until the present, enzyme replacement therapy of GSD Ib has not been developed, therefore, the main methods of treatment are a specialized diet with the addition of raw corn starch (for relief of hypoglycemia) and the use of granulocyte colony stimulating factor (for relief of neutropenia). However, the recent establishment of the role of 1,5-anhydroglucitol in the pathogenesis of neutrophil dysfunction in GSD Ib has led to a reprofiling of indications for the use of empagliflozin, a type 2 renal sodium—glucose cotransporter inhibitor (SGLT2). In the modern literature, it is reported about a minor, but very successful experience of its use in patients with GSD Ib (outside the framework of official indications for use) and a beneficial effect on neutrophil dysfunction and its clinical consequences. Oddly enough, this hypoglycemic drug improved not only metabolic, but also glycemic control in patients with GSD Ib, despite the fact that the pathology is based on chronic hypoglycemia. More and more evidence points to the role of empagliflozin in the regulation of cellular homeostasis (for example, fatty acid metabolism, glucose, cholesterol, apoptosis and cell proliferation, in particular in the liver) by influencing the activity of sirtuin 1 (SIRT1), AMP-activated protein kinase (AMPK) and signal molecules such as -serine/threonine protein kinase (Akt) and a mechanical target of rapamycin (mTOR), which leads to an improvement in the structure and function of mitochondria, stimulation of autophagy, reducing oxidative stress and suppressing inflammation. Modulation of these pathways shifts oxidative metabolism from carbohydrates to lipids and leads to a key decrease in insulin levels, resistance to it, glucose and lipotoxicity. This review presents current data on the pathogenesis of neutropenia and the possibility of using empagliflozin for its relief in patients with GSD Ib.